Pentingnya Pendidikan Anti Kekerasan Dalam Membentuk Generasi Damai - Utami, Salsabilla; Albina, Meyniar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the importance of anti-violence education as a preventive effort in reducing acts of violence in society through a human values-based approach, then this article reviews various methods that can be applied in the school, family and community environment. Non-violence education aims to form individuals who have empathy, tolerance and the ability to resolve conflicts peacefully. Anti-violence education has a strategic role in creating a generation that is able to live side by side peacefully and highlights the importance of this education as a preventive effort to reduce acts of violence that are currently occurring in society, hence the need for an approach that instills the values of empathy, tolerance and the ability to resolve conflicts effectively. constructive, anti-violence education can be applied in various environments, such as schools, families and communities so that individuals with peace-loving characters are formed in building a harmonious society free from violence.